Examining social policies in homelessness issues: Insight from Indonesian grassroots - Izudin, Ahmad (UIN Sunan Kalijaga Yogyakarta, 2023)
This article seeks social protection for people with homeless problems under Indonesian regional policies. My observation demonstrates although the social policies changed that help us comprehend homelessness concerns containing identification issues, urban bias, poverty validation, the cycle of change, quality of life, and prosecution, an identification issue on homeless remains a dilemma. Social policies should create integrated systems as the most important in urban alleviating poverty, social protection and empowerment, and referral mechanisms. Norms and principles of human dignity must provide to people who are trapped social vulnerable, while social protection should be combined between public and government support. Keywords Social Policy, Protecting Homeless Issues, Local Shelters, Urban Bias, Standard of Poverty Validation. Artikel ini mencari sistem perlindungan sosial bagi penyandang masalah gelandangan dan pengemis di bawah kebijakan daerah Indonesia. Pengamatan saya menunjukkan meskipun kebijakan sosial berubah yang membantu untuk memahami masalah tunawisma yang berisi masalah identifikasi, bias perkotaan, validasi kemiskinan, siklus perubahan, kualitas hidup, dan penuntutan, masalah identifikasi gelandangan dan pengemis tetap menjadi dilema. Kebijakan sosial harus menciptakan sistem terpadu sebagai bagian terpenting dalam pengentasan kemiskinan perkotaan, perlindungan dan pemberdayaan sosial, dan mekanisme rujukan secara jelas. Norma dan prinsip kemanusiaan harus diberikan kepada orang-orang yang terjebak oleh kerentanan sosial, dan perlindungan sosial harus dipadukan antara dukungan publik dan pemerintah. Kata Kunci: Kebijakan sosial, Perlindungan gelandangan, Shelter, Bias Perkotaan, Standar Validasi Kemiskinan